Self-perceived orthodontic need and perception towards fake braces among university students in Malaysia: preliminary findings - Mohd Nor, Nor Azlida; Kamarudin, Yasmin; Bahar, Aufa Dahlia; Cheong, Joo Ming; Mohd Nor, Norasmiha; Hamdan, Ruhil Hayati; Silahudin, Shafaatussara (International Association for Dental Research - Malaysian Section (IADR MalSec), 2022)
Background: Fake braces are fitted by unqualified individuals and have raised public concerns in Malaysia. This study aimed to explore self-perceived orthodontic needs and perceptions towards fake braces among university students in Malaysia. A cross-sectional study using self-administered questionnaire was distributed via Google Form. The data were analysed descriptively using SPSS. In total, 246 participants completed the questionnaire. Majority of them were female (68.3%) with a mean age of 21.74 (SD: ±1.08). More than half were Malay (56.1%) followed by other ethnicities. Only 44.3% of them were satisfied with their teeth appearance with 15.4% perceived they definitely need orthodontic treatment. Another 58.1% perceived they most probably needed orthodontic treatment. About 6.5% admitted have had experience wearing fake braces. Participants also reported having friends (27.6%) and family members (6.1%) wearing fake braces. Meanwhile, one third (33.7%) of them had searched for information about fake braces. Only a small proportion (8.1%) agreed with the benefit of fake braces in improving alignment of teeth, while the majority (67.5%) of them believe the risks of wearing fake braces were greater. There are mixed perceptions towards fake braces among Malaysian university students, with a minority favouring fake braces treatment.